DEVELOPMENT OF SIMPLE ANALYTICAL METHOD OF OMEGA-3 FATTY ACID BY PROPANOIC ACID DETERMINATION USING ALKALIMETRIC TITRATION - Sri Handayani; Cornelia Budimarwanti (Indonesian Journal of Chemistry, 2006)
The content of omega-3 in the fish oil capsules have been determined by alkalimetrie titration method. This method has been done in three ways. Firstly, fatty acids were oxidized by KMnO4 using H2SO4 as catalyst. Secondly, propanoic acid as the result of oxidation was separated by distillation. Furthermore, distillated propanoic acid was titrated. Precision, accuracy, repeatability, and reproducibility of the research were good enough for further development as a routine method for determination of omega-3 content.